2019
DOI: 10.5005/jp-journals-10071-23204
|View full text |Cite
|
Sign up to set email alerts
|

A Snapshot of Compliance with the Sepsis Six Care Bundle in Two Acute Hospitals in the West Midlands, UK

Abstract: Background The sepsis six care bundle has been adopted by hospitals in England and Wales for the management of patients with sepsis, with the aim of increasing survival when all elements of the bundle are achieved. Aim To assess compliance with the Sepsis Six Care Bundle in two acute NHS hospitals in the West Midlands. Materials and Methods Adults admitted to hospital over a 24-hour period were screened for sepsis. Sepsis was identified using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…With respect to compliance with SSCB, recent studies have indicated that very few patients received all the six interventions of the bundle within the recommended 1 h and the elements were not consistently applied [11]. This is in line with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…With respect to compliance with SSCB, recent studies have indicated that very few patients received all the six interventions of the bundle within the recommended 1 h and the elements were not consistently applied [11]. This is in line with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…The Sepsis Six Care Bundle (SSCB) was recently introduced into the maternity hospitals of the health region under examination in this study, in the form of a sticker on patients' notes, with the aim of delivering all six elements of the bundle (Additional file 1: Sepsis Six Sticker) within 1 h of sepsis being provisionally diagnosed. However, compliance has not been uniform and in line with the suggestions of SSCB [11].…”
Section: Introductionmentioning
confidence: 84%
“…To facilitate linkage to national databases for the collection of follow-up data, we collected patient-identifiable data and entered it on to the secure data collection tool 19 . Further description of the methodology and performance of this platform is outlined in previous publications 16 , 18 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Although high-profile cases and systematic campaign from advocacy groups helped to increase awareness of the condition in the last decade, there is very little data available on the progress and change of sepsis care outside the critical care environment in the UK 15 , 16 . While the use of sepsis screening tools and the delivery of the ‘Sepsis Six’ bundle is now a key performance indicator in many institutions, external scrutiny of such initiatives is lacking 17 , 18 . The aim of our study was to examine the changes in care processes and outcomes over a four-year period, by utilising our yearly All Wales point-prevalence study on sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most easily measured parameters is lactate. Measurement of lactate levels is still recommended by the Sepsis Six approach, initially developed in 2009 but still applied in recent years [19,20]. Sepsis Six is also an initial bundle that contributes to timely care including the administration of crystalloids, oxygen, antibiotics in the first hour along with microbiological sampling, measurement of urine output and lactate levels.…”
Section: Introductionmentioning
confidence: 99%